Probiotic VSL#3 Treatment Reduces Colonic Permeability and Abdominal Pain Symptoms in Patients With Irritable Bowel Syndrome - Prapaporn Boonma; Jordan Shapiro; Emily B. Hollister; Shyam Badu; Qinglong Wu; Erica M. Weidler; Bincy Abraham; Sridevi Devaraj; Ruth Ann Luna; James Versalovic; Margaret Heitkemper; Tor Savidge; et al. (Frontiers in Pain Research, 2021)
www.clinicaltrials.gov, Identifier: NCT00971711.
Keywords: Gastrointestinal motility and disorders; Gut microbiota and health; Probiotics and Fermented Foods